Human Virtuality and Digital Life. Philosophical and Psychoanalytic Investigations. Primera edición. Routledge. Taylor & Francis Group, 2021, 296 pp. (314 pp.; edición digital) - Krebs, Victor J. (2022)
No presenta resumen